A bismuth ferrite-based lead-free high-entropy energy storage ceramic material and a preparation method thereof

CN117594353BActive Publication Date: 2026-10-09GUANGZHOU INST OF ADVANCED MATERIALS UNIV OF SCI & TECH BEIJING
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311588817.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-27
Publication Date
2026-10-09
Estimated Expiration
2043-11-27

AI Technical Summary

Technical Problem

其中铁电材料,由于其具有高的饱和极化强度而具有潜力获得高的储能特性,但是其大的剩余极化强度不利于其储能性能,并且长期以来,铅基铁电材料如锆钛酸铅等固溶体因具有优异的电学性能、力学性能、良好的热稳定性等优点占据应用市场的主导地位,但是铅元素对对环境以及人体有害

Benefits of technology

[0017] 1. The ceramic composition of the present invention has both high energy storage density and high energy storage efficiency, and can be obtained using traditional piezoelectric ceramic preparation technology and industrial raw materials, with low cost and practicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117594353B_ABST
    Figure CN117594353B_ABST
Patent Text Reader

Abstract

The application provides a bismuth ferrite-based lead-free high-entropy energy storage ceramic material and a preparation method, belongs to the field of dielectric energy storage ceramic materials, and is applied to a pulse power capacitor. 0.5 Ba 0.1 Sr 0.1 Ca 0.2 Na 0.1 )(Fe 0.5 Ti 0.3 Zr 0.1 Nb 0.1 )O3. The bismuth ferrite-based lead-free high-entropy energy storage ceramic material has high energy storage density and high energy storage efficiency, and can meet the practical application requirements in lead-free energy storage capacitors by utilizing the advantages of large spontaneous polarization of the ferroelectric BiFeO3, adding other different tolerance factors and ion polarization perovskite compositions to BiFeO3 by using a high-entropy strategy, and introducing ions with different valences and radii at A and B sites to obtain a stable relaxor ferroelectric phase structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of dielectric energy storage ceramic materials, specifically relating to a bismuth ferrite-based lead-free high-entropy energy storage ceramic material and its preparation method. Background Technology

[0002] Pulsed power systems have a wide range of applications, playing a vital role in fields such as national defense, biology, and medicine. Pulsed capacitors, as energy storage elements, are extremely important components in these systems. Based on their energy storage principles, they can be categorized into inductive energy storage, capacitor energy storage, inertial energy storage, and chemical energy storage. Among these, capacitor energy storage utilizes the polarization of a dielectric material caused by an electric field. It boasts advantages such as ultra-high power density, fast charging and discharging speeds, flexible combination, mature technology, low cost, and a wide applicable temperature and frequency range, making it the most widely used energy storage method currently.

[0003] In recent years, with the development of pulsed power supplies towards higher power, higher repetition frequency, and miniaturization, pulse capacitors are required to have high energy density, a service life matching the load life, and high reliability. This makes maximizing energy density while meeting life requirements the research goal of high-performance pulse capacitors. However, the energy density of dielectric capacitors is typically low (≤1 J / cm³). 3 However, this approach cannot meet the needs of integration and miniaturization, severely limiting its further application. The energy storage element supporting a pulsed power system is the pulsed power capacitor, and the dielectric material determines the output characteristics of the pulsed power capacitor. Currently, research on high-energy-density dielectric materials for capacitor fabrication mainly focuses on three categories: polymers, polymer-ceramic composites, and ceramics. Among them, ceramic materials have advantages such as high operating temperature, high dielectric constant, relatively high dielectric strength, low loss, high energy density, and ease of mass production, making them particularly suitable as dielectric materials for pulsed power capacitors. Furthermore, ceramic capacitors operate under breakdown field strength without self-healing-induced capacitance reduction; therefore, as long as they do not break down, they can have a considerably long charge-discharge life. Moreover, ceramic materials are inorganic, have a long storage time, and do not deteriorate or age. In addition, ceramic materials are widely available, diverse in type, and ceramic powder formulations can be adjusted to meet different performance requirements.

[0004] Energy storage ceramic dielectric materials can be mainly classified into three categories: linear ceramic dielectrics, ferroelectric ceramic dielectrics, and antiferroelectric ceramic dielectrics. Ferroelectric materials, due to their high saturation polarization, have the potential to achieve high energy storage characteristics; however, their large remanent polarization is detrimental to their energy storage performance. Furthermore, lead-based ferroelectric materials, such as lead zirconate titanate solid solutions, have long dominated the application market due to their excellent electrical and mechanical properties and good thermal stability. However, lead is harmful to the environment and human health. Considering current concerns about environmental issues and the polluting effects of lead and its compounds, developing high-performance lead-free energy storage ceramics for use in pulse capacitors is of significant practical importance. Summary of the Invention

[0005] To address the aforementioned issues, this invention provides a bismuth ferrite-based lead-free high-entropy energy storage ceramic material and its preparation method. Utilizing the advantage of the large spontaneous polarization of ferroelectric BiFeO3, a high-entropy strategy is employed to add perovskite components with different tolerance factors and ionic polarizations to BiFeO3. Simultaneously, ions with different valence states and radii are introduced at the A and B sites to obtain a stable relaxor ferroelectric phase structure. Ultimately, a bismuth ferrite-based lead-free high-entropy energy storage ceramic material with both high energy density and high energy storage efficiency is obtained, enabling it to meet the practical application requirements of lead-free energy storage capacitors.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] This invention provides a bismuth ferrite-based lead-free high-entropy energy storage ceramic material for use in pulse power capacitors, with a chemical composition of (Bi... 0.5 Ba 0.1 Sr 0.1 Ca 0.2 Na 0.1 (Fe) 0.5 Ti 0.3 Zr 0.1 Nb 0.1 )O3.

[0008] This invention provides a method for preparing the above-mentioned bismuth ferrite-based lead-free high-entropy energy storage ceramic material, comprising the following steps: S1. Weighing raw materials of metal carbonate or oxide according to stoichiometric ratio, mixing and calcining once to obtain pre-synthesized powder; S2. High-energy ball milling of the pre-synthesized powder, mixing and granulating, sieving and pressing into tablets, and sintering to obtain a ceramic sample; S3. Polishing the ceramic sample, cleaning and drying, coating both ends with silver paste, and calcining a second time.

[0009] Furthermore, in step S1, the mixing process involves ball milling the metal carbonate or oxide with alcohol or water as the medium for 8-12 hours at a speed of 200-400 r / min, followed by drying after ball milling.

[0010] Furthermore, the process parameters for the first calcination are as follows: the dried mixed raw materials are calcined in an oxidizing environment at a synthesis temperature of 750-850℃ for 4-5 hours.

[0011] Furthermore, in step S2, the process parameters for the high-energy ball milling are as follows: the pre-synthesized powder is ball-milled for 8-12 hours using alcohol or water as the medium at a speed of 500-700 r / min, and then dried after high-energy ball milling.

[0012] Furthermore, after drying, the D50 particle size of the powder is 3.5-4.5μm, and the D40 / D50 ratio is 1.0-1.2.

[0013] Furthermore, the dried powder is mixed with a binder and granulated, then passed through a 100-150 mesh sieve and cold-pressed under a pressure of 200-300 MPa to obtain a ceramic green body.

[0014] Furthermore, the ceramic ligand is sintered in an oxidizing environment under normal pressure using a powder embedding method, with the temperature increased to 500-600℃ at a heating rate of 2-4℃ / min and held for 25-35min, then increased to 950-1050℃ at a heating rate of 4-6℃ / min and sintered for 2-3h. After sintering, it is cooled in the furnace.

[0015] Furthermore, the process parameters for the secondary calcination are: calcining silver in an oxidizing environment at 550-650℃ for 30-60 minutes.

[0016] The beneficial effects of the technical solutions provided by the embodiments of the present invention include:

[0017] 1. The ceramic composition of the present invention has both high energy storage density and high energy storage efficiency, and can be obtained using traditional piezoelectric ceramic preparation technology and industrial raw materials, with low cost and practicality.

[0018] 2. Compared to conventional binary and tri-energy ceramic compositions with solid solutions, this invention utilizes a high-entropy strategy to significantly improve the overall energy storage performance of lead-free energy storage ceramics, and can simultaneously control high W... rec High η, High E b short t 0.9 medium ε r It is a lead-free energy storage ceramic material with low tanσ, which has excellent performance, meets the application requirements of pulse power capacitors, and has good process repeatability, no other impurities, and good performance stability.

[0019] 3. This method provides a new approach for designing and preparing high-performance lead-free energy storage ceramics, with extremely high performance tunability, and can be applied to various energy storage ceramic systems. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 The image shows the XRD pattern of the bismuth ferrite-based lead-free high-entropy energy storage ceramic material prepared in Example 1 of this invention.

[0022] Figure 2 This is a SEM image of the surface morphology of the bismuth ferrite-based lead-free high-entropy energy storage ceramic material prepared in Example 1 of this invention.

[0023] Figure 3 This is a graph showing the energy storage performance of the bismuth ferrite-based lead-free high-entropy energy storage ceramic material prepared in Example 1 of this invention. a represents W. rec The graph shows the relationship between η and electric field, where b is ε. r The graph shows the change of tanσ with temperature. The solid line represents the relative permittivity, and the dashed line represents the dielectric loss. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0025] This invention discloses a bismuth ferrite-based lead-free high-entropy energy storage ceramic material for use in pulse power capacitors, with a chemical composition of (Bi... 0.5 Ba 0.1 Sr 0.1 Ca 0.2 Na 0.1 (Fe) 0.5 Ti 0.3 Zr 0.1 Nb 0.1 )O3.

[0026] Bismuth ferrite (BiFeO3) exhibits a large polarization intensity at room temperature (~90-100 μC / cm). 2 ) and high Curie temperature T C(~823℃) has a natural advantage in the design of high-performance lead-free dielectric energy storage materials. However, pure-phase BiFeO3 is difficult to prepare, and usually has a second phase that is detrimental to electrical performance; it also suffers from problems such as high remanent polarization, low high-temperature conductivity, and high losses, which are not conducive to its application as a dielectric energy storage material. To address these issues and further improve the energy storage performance of ceramic capacitors, a high-entropy strategy is adopted to design a lead-free high-entropy energy storage ceramic with excellent comprehensive performance, namely: (Bi 0.5 Ba 0.1 Sr 0.1 Ca 0.2 Na 0.1 (Fe) 0.5 Ti 0.3 Zr 0.1 Nb 0.1 On the one hand, the high-entropy strategy has strong operability in the design of local polarization configurations of ferroelectrics, and can effectively design local structures that match the structural characteristics required for high energy storage performance. This scheme uses BiFeO3 as the main phase (50% content), retaining the advantages of the BiFeO3 system in terms of high polarization intensity and excellent temperature stability. At the same time, it introduces lead-free perovskite systems (BaTiO3, CaTiO3, CaZrO3, SrTiO3, NaNbO3) with different average polarizabilities and tolerance factors in the same content (10%) into the BiFeO3 matrix, effectively improving the difficulty of BiFeO3 preparation and maximizing the entropy value of the system. According to first-principles calculations, high entropy in ferroelectric systems will effectively enhance local polarization disorder. Entropy increase improves the sensitivity to external field response. It makes the polarization intensity and polarization angle distribution more diffuse, reduces polarization anisotropy, and significantly reduces the residual polarization intensity of BiFeO3, which is beneficial to obtaining excellent energy storage performance. On the other hand, this design idea can also introduce a variety of ions with different ionic radii and valence states into the antiferroelectric lattice to achieve entropy increase, enhance structural disorder and random electric field, reduce residual polarization, reduce the size of polar nanoregions, reduce losses when working under strong electric fields, enhance breakdown electric field and delay polarization saturation, and obtain energy storage ceramics with high energy density and high efficiency.

[0027] This invention also proposes a method for preparing the above-mentioned bismuth ferrite-based lead-free high-entropy energy storage ceramic material, comprising the following steps:

[0028] S1. Weigh the raw materials of metal carbonate or oxide according to the stoichiometric ratio, mix them and calcine them once to obtain the pre-synthesized powder.

[0029] The mixing process involves: ball milling the metal carbonate or oxide with alcohol or water as the medium for 8-12 hours at a speed of 200-400 r / min, followed by drying after ball milling; the process parameters for the first calcination are: calcining the dried mixed raw materials in an oxidizing environment at a synthesis temperature of 750-850℃ for 4-5 hours to obtain the pre-synthesized powder.

[0030] This invention targets a chemical composition of (Bi) 0.5 Ba 0.1 Sr 0.1 Ca 0.2 Na 0.1 (Fe) 0.5 Ti 0.3 Zr 0.1 Nb 0.1 The material for O3 is selected from carbonate or oxide raw materials, such as Bi2O3, Ba2CO3, TiO2, CaCO3, Na2CO3, SrCO3, ZrO2, Fe2O3 or NbO2; the alcohol is preferably anhydrous ethanol.

[0031] To improve the oxidation degree of the raw materials, the preferred oxidation environment of the present invention is an oxygen flow rate of 40-50 mL / min.

[0032] S2. The pre-synthesized powder is subjected to high-energy ball milling, mixed and granulated, sieved, pressed into tablets, and sintered to obtain a ceramic sample.

[0033] The high-energy ball milling process parameters are as follows: the pre-synthesized powder is ball-milled for 8-12 hours using alcohol or water as the medium at a speed of 500-700 r / min, and then dried. After drying, the D50 particle size of the powder is 3.5-4.5 μm, and the D40 / D50 ratio is 1.0-1.2. The dried powder is mixed with a binder and granulated, with the binder being 0.5 wt% PVB of the powder mass. After passing through a 100-150 mesh sieve, it is cold-pressed under a pressure of 200-300 MPa to obtain a ceramic green body. The ceramic ligand is sintered in an oxidizing environment at normal pressure using a powder embedding method, heated to 500-600℃ at a heating rate of 2-4℃ / min and held for 25-35 min, then heated to 950-1050℃ at a heating rate of 4-6℃ / min and sintered for 2-3 hours. After sintering, it is cooled in the furnace to obtain the ceramic sample.

[0034] This invention produces a circular sheet with a diameter of 10 mm and a thickness of 1 mm by cold pressing.

[0035] By controlling the high-energy ball milling process, the particle size of the powder can be controlled within a certain range, resulting in higher density of the subsequently prepared ceramic samples, improved breakdown field strength, and thus greater energy storage density. At the same time, it also has a certain impact on the microstructure and ferroelectric properties of the ceramic material.

[0036] S3. Polish the ceramic sample, clean and dry it, apply silver paste to both ends, and then calcine it a second time.

[0037] The process parameters for the secondary calcination are: calcining silver in an oxidizing environment at 550-650℃ for 30-60 minutes.

[0038] To better illustrate the embodiments of the present invention, the present invention will be further described in detail below through specific examples.

[0039] Example 1

[0040] The embodiments of the present invention provide (Bi) 0.5 Ba 0.1 Sr 0.1 Ca 0.2 Na 0.1 (Fe) 0.5 Ti 0.3 Zr 0.1 Nb 0.1 The preparation method of O3 includes the following steps:

[0041] S1. Weigh the raw materials of metal carbonates or oxides according to the stoichiometric ratio, mix them, and calcine them once to obtain a pre-synthesized powder. The metal carbonates or oxides are ball-milled for 10 hours at a speed of 300 r / min using alcohol or water as the medium, and then dried after ball milling. The process parameters for the first calcination are as follows: calcine the dried mixed raw materials in an oxidizing environment at a synthesis temperature of 850℃ for 5 hours to obtain the pre-synthesized powder.

[0042] S2. The pre-synthesized powder is subjected to high-energy ball milling, mixed and granulated, sieved, pressed into tablets, and sintered to obtain a ceramic sample. The process parameters for high-energy ball milling are as follows: the pre-synthesized powder is ball-milled for 10 hours with alcohol or water as the medium at a speed of 500 r / min, and then dried after high-energy ball milling. After drying, the D50 particle size of the powder is 2.0 μm, and the D40 / D50 ratio is 1.0. The dried powder is mixed with a binder and granulated, sieved through a 100-150 mesh sieve, and then cold-pressed under a pressure of 200 MPa to obtain a ceramic green body. The ceramic ligand is sintered in an oxidizing environment at normal pressure using a powder embedding method, heated to 550℃ at a heating rate of 3℃ / min and held for 30 min, then heated to 1000℃ at a heating rate of 5℃ / min and sintered for 3 hours. After sintering, it is cooled in the furnace to obtain the ceramic sample.

[0043] S3. Polish the ceramic sample, clean and dry it, apply silver paste to both ends, and then calcine it a second time.

[0044] The process parameters for the secondary calcination are: calcining silver in an oxidizing environment at 550-650℃ for 30 minutes.

[0045] Figure 1 The image shows the XRD pattern of the bismuth ferrite-based lead-free high-entropy energy storage ceramic material prepared in the embodiments of the present invention, which can be seen to have a cubic phase structure.

[0046] Figure 2 The image shows the surface SEM morphology of the bismuth ferrite-based lead-free high-entropy energy storage ceramic material prepared in this embodiment of the invention, which has a dense microstructure.

[0047] like Figure 3 As shown in a, the energy storage ceramic material prepared by this invention simultaneously possesses high energy storage density and high energy storage efficiency; as shown in a diagram. Figure 3 As shown in b, a relaxation phase transition occurs with increasing temperature, and the dielectric constants at different frequencies are relatively similar. In addition, the dielectric loss is low from room temperature to around 200°C.

[0048] Measurements show that the ceramic sample prepared in this invention can release a storage energy density W. rec 13.3 J / cm 3 The energy storage efficiency η is 78%, and the breakdown field strength E b The discharge voltage is 664 kV / cm, and the discharge time is t. 0.9 The relative permittivity ε is 17 ns. r The value is 418, and the dielectric loss tanσ is 0.012.

[0049] Example 2

[0050] The embodiments of the present invention provide (Bi) 0.5 Ba 0.1 Sr 0.1 Ca 0.2 Na 0.1 (Fe) 0.5 Ti 0.3 Zr 0.1 Nb 0.1 The preparation method of O3 includes the following steps:

[0051] S1. Weigh the raw materials of metal carbonates or oxides according to the stoichiometric ratio, mix them, and calcine them once to obtain a pre-synthesized powder. The metal carbonates or oxides are ball-milled for 8 hours at a speed of 200 r / min using alcohol or water as the medium, and then dried after ball milling. The process parameters for the first calcination are as follows: calcine the dried mixed raw materials in an oxidizing environment at a synthesis temperature of 750℃ for 4 hours to obtain the pre-synthesized powder.

[0052] S2. The pre-synthesized powder is subjected to high-energy ball milling, mixed and granulated, sieved, pressed into tablets, and sintered to obtain a ceramic sample. The process parameters for high-energy ball milling are as follows: the pre-synthesized powder is ball-milled for 8 hours with alcohol or water as the medium at a speed of 500 r / min, and then dried after high-energy ball milling. After drying, the D50 particle size of the powder is 4.4 μm, and the D40 / D50 ratio is 1.2. The dried powder is mixed with a binder and granulated, sieved through a 100-150 mesh sieve, and then cold-pressed under a pressure of 200 MPa to obtain a ceramic green body. The ceramic ligand is sintered in an oxidizing environment at normal pressure using a powder embedding method, heated to 500℃ at a heating rate of 2℃ / min and held for 25 min, then heated to 950℃ at a heating rate of 4℃ / min and sintered for 2 hours. After sintering, it is cooled in the furnace to obtain the ceramic sample.

[0053] S3. Polish the ceramic sample, clean and dry it, apply silver paste to both ends, and then calcine it a second time.

[0054] The process parameters for the secondary calcination are: calcining silver in an oxidizing environment at 550-650℃ for 30 minutes.

[0055] The ceramic sample prepared in this embodiment has a cubic phase structure, free of any other impurities, and exhibits a dense microstructure. The ceramic sample prepared by this invention can release a storage density W. rec 12.8 J / cm 3 The energy storage efficiency η is 78%, and the breakdown field strength E b The discharge voltage is 535 kV / cm, and the discharge time is t. 0.9 The relative permittivity ε is 17 ns. r The value is 423, and the dielectric loss tanσ is 0.015.

[0056] Example 3

[0057] The embodiments of the present invention provide (Bi) 0.5 Ba 0.1 Sr 0.1 Ca 0.2 Na 0.1 (Fe) 0.5 Ti 0.3 Zr 0.1 Nb 0.1 The preparation method of O3 includes the following steps:

[0058] S1. Weigh the raw materials of metal carbonates or oxides according to the stoichiometric ratio, mix them, and calcine them once to obtain a pre-synthesized powder. The metal carbonates or oxides are ball-milled for 12 hours at a speed of 400 r / min using alcohol or water as the medium, and then dried after ball milling. The process parameters for the first calcination are as follows: calcine the dried mixed raw materials in an oxidizing environment at a synthesis temperature of 850℃ for 5 hours to obtain the pre-synthesized powder.

[0059] S2. The pre-synthesized powder is subjected to high-energy ball milling, mixed and granulated, sieved, pressed into tablets, and sintered to obtain a ceramic sample. The process parameters for high-energy ball milling are as follows: the pre-synthesized powder is ball-milled for 12 hours with alcohol or water as the medium at a speed of 700 r / min, and then dried after high-energy ball milling. After drying, the D50 particle size of the powder is 3.5 μm, and the D40 / D50 ratio is 1.2. The dried powder is mixed with a binder and granulated, sieved through a 100-150 mesh sieve, and then cold-pressed under a pressure of 300 MPa to obtain a ceramic green body. The ceramic ligand is sintered in an oxidizing environment at normal pressure using a powder embedding method, heated to 600℃ at a heating rate of 4℃ / min and held for 35 min, then heated to 1050℃ at a heating rate of 6℃ / min and sintered for 3 hours. After sintering, it is cooled in the furnace to obtain the ceramic sample.

[0060] S3. Polish the ceramic sample, clean and dry it, apply silver paste to both ends, and then calcine it a second time.

[0061] The process parameters for the secondary calcination are: calcining silver in an oxidizing environment at 550-650℃ for 60 minutes.

[0062] The ceramic sample prepared in this embodiment has a cubic phase structure, free of any other impurities, and exhibits a dense microstructure. The ceramic sample prepared by this invention can release a storage density W. rec 12.9 J / cm 3 The energy storage efficiency η is 76%, and the breakdown field strength E b The discharge voltage is 515 kV / cm, and the discharge time is t. 0.9 The relative permittivity ε is 19 ns. r The value is 412, and the dielectric loss tanσ is 0.013.

[0063] Comparative Example 1

[0064] Unlike Example 1, in this comparative example, the powder prepared in step S2 has a D50 particle size of 3.2 μm and a D40 / D50 ratio of 1.1.

[0065] The ceramic sample prepared in this comparative example has a cubic phase structure, free of any other impurities, and exhibits a dense microstructure. The ceramic sample prepared in this invention can release a storage density W. rec 10.8 J / cm3 The energy storage efficiency η is 78%, and the breakdown field strength E b The discharge voltage is 596 kV / cm, and the discharge time is t. 0.9 The relative permittivity ε is 17 ns. r The value is 421, and the dielectric loss tanσ is 0.014.

[0066] Comparative Example 2

[0067] Unlike Example 1, in this comparative example, the powder prepared in step S2 has a D50 particle size of 4.8 μm and a D40 / D50 ratio of 1.2.

[0068] The ceramic sample prepared in this comparative example has a cubic phase structure, free of any other impurities, and exhibits a dense microstructure. The ceramic sample prepared in this invention can release a storage density W. rec 9.0 J / cm 3 The energy storage efficiency η is 77%, and the breakdown field strength E b The voltage is 547 kV / cm, and the discharge time is t. 0.9 The relative permittivity ε is 19 ns. r The value is 411, and the dielectric loss tanσ is 0.013.

[0069] By comparing Example 1, Comparative Examples 1 and 2, it can be seen that by controlling the D50 particle size of the powder to be 3.5-4.5 μm and the D40 / D50 to be 1.0-1.2, the energy storage density of the prepared energy storage ceramic can be increased, the breakdown field strength can be increased, and the dielectric loss can be reduced, thus improving the energy storage performance.

[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A bismuth ferrite-based lead-free high-entropy energy storage ceramic material, used in pulse power capacitors, characterized in that... The chemical composition is (Bi) 0.5 Ba 0.1 Sr 0.1 Ca 0.2 Na 0.1 (Fe) 0.5 Ti 0.3 Zr 0.1 Nb 0.1 )O3.

2. A method for preparing a bismuth ferrite-based lead-free high-entropy energy storage ceramic material as described in claim 1, characterized in that, Includes the following steps: S1. Weigh the raw materials of metal carbonate or oxide according to the stoichiometric ratio, mix them and calcine them once to obtain the pre-synthesized powder; S2. The pre-synthesized powder is subjected to high-energy ball milling, mixed and granulated, sieved, pressed into tablets, and sintered to obtain a ceramic sample; S3. Polish the ceramic sample, clean and dry it, apply silver paste to both ends, and then calcine it a second time.

3. The preparation method of the bismuth ferrite-based lead-free high-entropy energy storage ceramic material according to claim 2, characterized in that, In step S1, the mixing process involves ball milling the metal carbonate or oxide with alcohol or water as the medium for 8-12 hours at a speed of 200-400 r / min, followed by drying after ball milling.

4. The preparation method of the bismuth ferrite-based lead-free high-entropy energy storage ceramic material according to claim 3, characterized in that, The process parameters for the first calcination are as follows: the dried mixed raw materials are calcined in an oxidizing environment at a synthesis temperature of 750-850℃ for 4-5 hours.

5. The method for preparing bismuth ferrite-based lead-free high-entropy energy storage ceramic material according to claim 2, characterized in that, In step S2, the process parameters for high-energy ball milling are as follows: the pre-synthesized powder is ball-milled for 8-12 hours with alcohol or water as the medium at a speed of 500-700 r / min, and then dried after high-energy ball milling.

6. The method for preparing the bismuth ferrite-based lead-free high-entropy energy storage ceramic material according to claim 5, characterized in that, After drying, the D50 particle size of the powder is 3.5-4.5μm, and the D40 / D50 ratio is 1.0-1.

2.

7. The method for preparing the bismuth ferrite-based lead-free high-entropy energy storage ceramic material according to claim 5, characterized in that, The dried powder is mixed with a binder and granulated. After passing through a 100-150 mesh sieve, it is cold-pressed under a pressure of 200-300 MPa to obtain a ceramic green body.

8. The method for preparing the bismuth ferrite-based lead-free high-entropy energy storage ceramic material according to claim 7, characterized in that, The ceramic green body is sintered in an oxidizing environment under normal pressure using the powder embedding method. The temperature is increased to 500-600℃ at a heating rate of 2-4℃ / min and held for 25-35min. The temperature is then increased to 950-1050℃ at a heating rate of 4-6℃ / min and sintered for 2-3h. After sintering, the green body is cooled in the furnace.

9. The method for preparing the bismuth ferrite-based lead-free high-entropy energy storage ceramic material according to claim 2, characterized in that, The process parameters for the secondary calcination are: calcining silver in an oxidizing environment at 550-650℃ for 30-60 minutes.

Citation Information

Patent Citations

  • High-entropy perovskite oxide doped ceramic, preparation method and application thereof

    CN115991599A

  • Method for preparing crystalline state perovskite compounds powder

    CN1524792A